Effect of vitamin D3 on the osteogenic differentiation of human periodontal ligament stromal cells under inflammatory conditions. (5th February 2021) - Blufstein, Alice; Behm, Christian; Kubin, Barbara; Gahn, Johannes; Rausch‐Fan, Xiaohui; Moritz, Andreas; Andrukhov, Oleh
Abstract: Objectives: Vitamin D3 is known to activate osteogenic differentiation of human periodontal ligament stromal cells (hPDLSCs). Recently, inflammatory stimuli were shown to inhibit the transcriptional activity of hPDLSCs, but their effect on vitamin D3 ‐induced osteogenic differentiation is not known. The present study aimed to investigate whether the effects of 1, 25‐dihydroxvitamin D3 (1, 25(OH)2 D3 ) and 25‐hydroxvitamin D3 (25(OH)D3 ) on the osteogenic differentiation of hPDLSCs are also altered under inflammatory conditions. Furthermore, the expression of osteogenesis‐related factors by hPDLSCs under osteogenic conditions was assessed in the presence of inflammatory stimuli. Materials and Methods: Primary hPDLSCs of six donors were cultured in osteogenic induction medium containing either 1, 25(OH)2 D3 (0‐10 nM) or 25(OH)D3 (0‐100 nM) in the presence and absence of Porphyromonas gingivalis lipopolysaccharide (LPS) or Pam3CSK4 for 7, 14 and 21 days. Osteogenic differentiation of hPDLSCs was evaluated by analysis of mineralization as assessed by Alizarin Red S staining and gene expression levels of osteogenesis‐related factors osteocalcin, osteopontin and runt‐related transcription factor 2 (RUNX2) were analysed with qPCR. Results: Treatment with 1, 25(OH)2 D3 significantly enhanced the osteogenic differentiation of hPDLSCs and their expression of osteocalcin and osteopontin. The 1, 25(OH)2 D3 ‐triggered expression of osteogenesis‐related factors was significantly lower in the presence of Pam3CSK4, but not P .  gingivalis LPS. None of the inflammatory stimuli had significant effects on the 1, 25(OH)2 D3 ‐induced osteogenic differentiation. 25(OH)D3 neither affected gene expression levels nor osteogenic differentiation of hPDLSCs cultured in osteogenic induction medium. Conclusion: The results of this study indicate that inflammatory stimuli also diminish the 1, 25(OH)2 D3 ‐induced expression of osteogenesis‐related factors in hPDLSCs under osteogenic conditions, while having no effect on the osteogenic differentiation.